Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kalanduyung (Guazuma ulmifolia Lam.) terhadap Pertumbuhan Staphylococcus aureus dengan Metode Difusi Cakram (Kirby-Bauer) - Adelgrit Trisia; Regina Philyria; Angeline Novia Toemon (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Pneumonia is an infectious lung parenchyma, respiratory bronchioles, and alveolus, caused by Staphylococcus aureus. Kalanduyung (Guazuma ulmifolia Lam.) is an herb plant from Central Borneo which people believe has many benefits, which one is curing pneumonia. To identify the antibacterial activity from the ethanol extract of Kalanduyung leaves to the Staphylococcus aureus growth. This research was experimental with posttest-only control group design. Ethanol extract of Kalanduyung leaves in 20%, 40%, 60%, and 80% concentrations were tested for antibacterial capability against Staphylococcus aureus with Kirby Bauer disc diffusion method, with Amoxicillin as the positive control and 10% Dimethyl Sulfoxide. This data was statistically analyzed with One Way Anova. Ethanol extract of Kalanduyung leaves can inhibit Staphylococcus aureus with each inhibition zone diameter was 6.875 mm, 8.5 mm, 10.175 mm, and 14.925 mm. The ethanol extract of Kalanduyung leaves can inhibit the growth of Staphylococcus aureus bacteria.